Simulation of Sediment Transport rate using MIKE Software(Case Study:Karri port, Bushehr Province) - Mohammad Sadeghi; Masoud Torabi Azad; Tayeb Sadeghifar (Nīvār)
One of the most important and critical points in the study and design of marine structures is conducting hydrodynamic studies (including wind, wave, and current studies). The purpose of this research is to investigate the mechanism of sedimentation in Karri Port under the effect of tidal currents and wind waves. The importance of this issue is in the implementation of numerical models on small and large water areas for future predictions. Modeling of water level and flow changes in the studied area was done using a hydrodynamic module (HD) of MIKE 21 software and modeling of waves was done by spectral wave module (SW). The obtained results for currents and waves were evaluated and validated using the available implemented information. The predominant direction of the waves is from the northwest and south. The LITDRIFT module from LITPACK software package and MIKE21-ST module was used for one-dimensional and two-dimensional sediment modeling, respectively. The one-dimensional sediment transfer potential was found to be about 33,000 cubic meters per year. With the location of the breakwater opening towards the south and located in the front part of the beach of Karri village, the amount of sediment settling is not considered a problem for the Karri breakwater. The back of the main arm of the breakwater (north) does not have the problem of sediment accumulation and transfer to the south for the lifetime of the structure. Calibration of the numerical model for the flow and sedimentation pattern in the Karri Port mouth provides agreement of the numerical results with the experimental relations of C.E.R.C and Kamphuis.